Application of thermal detector by infrared for electrical arch furnaces transformer - Laohasongkram, Phiphat; Junsiri, Jakkrit; Oupayaso, Jakkrit (My University, 2007)
Infrared thermo graphic detector for non-contact temperature measurement is used in this project. Infrared thermometers will give an accurate temperature measurement if the emissivity of the thermometer is adjusted to fit with the emissivity of the measured material. Therefore, to use the infrared to measure the temperature of Electrical Arch Furnaces (EAF) transformer at steel industry, the optimal emissivity of this thermometer must be determined. However the emissivity of the bus bars in the transformer at which the temperature is measured is unknown. Therefore this study is conducted to determine the optimal emissivity of the infrared thermometer to get the accurate temperature measurement. Its application the radiometric thermo graphic system VarioCAM head for control and monitoring of the steel industrial process is installed and this emissivity is set up. © ICROS.
Keywords: Electrical Arch Furnaces (EAF) transformer; Infrared temperature measurement; Infrared thermometer